Itraconazole vs fluconazole as a primary prophylaxis for fungal infections in HIV-infected patients in Thailand - Chaiwarith R. (2014)
Background: Disseminated fungal infections are common presenting opportunistic infections among AIDS patients in developing countries. Primary prophylaxis with itraconazole has been shown to be effective in northern Thailand. This study aimed to compare the efficacy of fluconazole vs itraconazole as primary prophylaxis for fungal infections in HIV-infected patients. Methods: A retrospective cohort study was conducted among HIV-infected patients who received primary prophylaxis with fluconazole 400 mg once weekly or itraconazole 200 mg once daily at Chiang Mai University Hospital. We compared the incidence of systemic fungal infections and the probability of disease-free survival between groups. Results: From January 2000 to June 2010, 308 HIV-infected patients who received primary fungal prophylaxis were enrolled; 148 were male (48.1%) and the mean age was 38.2 ± 8.0 years. 276 patients received fluconazole and 32 received itraconazole. Baseline CD4+ cell count was 35 (IQR 15, 70) and 50 (IQR 21,75) cells/mm3 in fluconazole and itraconazole groups, respectively (p=0.159). The median follow-up time was 12 months (IQR 7, 19) in fluconazole group and 15.5 months (IQR 9, 21.5) in itraconazole group. Seven patients (2.5%) who received fluconazole and 2 patients (6.3%) who received itraconazole developed systemic fungal infections, giving the incidence of 17.0 and 34.8/10000 person-months, respectively (p=0.261). The probability of developing any systemic fungal infections or death did not differ between groups. Conclusions: Although P. marneffei has a reduced susceptibility in in vitro to fluconazole, our study has demonstrated that once-weekly fluconazole is at least as effective as once-daily itraconazole as primary prophylaxis for systemic fungal infections in AIDS patients in northern Thailand. © 2011 Bentham Science Publishers.